Conta livre x conta imposta: o efeito da reatância na satisfação dos consumidores bancários - Carvalho, Joana Rosa Cardoso de (2022)
Banking services have gained notoriety over the years due to the spread of financial importance. Consumers are increasingly empowered on their needs and expectations of services. Psychological reactance plays an important role in understanding consumers' reactive behavior regarding the threat to their freedom of choice. Since the threat to freedom is a predictor of dissatisfaction and negative behavior towards the service offered, understanding its influence on satisfaction is important to obtain long-term relationships and achieve consumer loyalty. The main objective of this work is to identify the moderating role of reactance in satisfaction regarding account types and its influence on the loyalty of banking services. Thus, we carried out a survey with a convenience sample and analyzed data using Structural Equation Modeling, and the SmartPLS 3.0 software. The sample consists of 267 respondents and the results of the analysis corroborate the theory presented, as the proposed hypotheses were confirmed. The theoretical contribution brings the evaluation of the relationship between the types of account and satisfaction, moderated by reactance, a context that no study has addressed before, therefore, we sought to fill this gap. For practice management, it is necessary to classify account types and the profile of consumers with high or low reactance to bank services. This work also presents propositions for future research and its limitations.